STUDENTS' PERCEPTIONS OF USING YOUTUBE VIDEO PROJECT FOR VOCABULARY LEARNING - Dhevia Shanati Firda; Sulistyani; Khoiriyah (STKIP AL HIKMAH SURABAYA, 2026)
This study aims to describe students' perceptions of YouTube Video Project in learning English vocabulary for tenth-grade students of SMAN 4 Kediri. This study was motivated by the limited use of YouTube as an active production media in English learning where students generally act only passive consumers of information. This study used a qualitative descriptive approach that involved five students from grade X-3 who were selected using purposive sampling. The data were collected through observation, semi-structured interviews, and documentation. The results showed that students had very positive perceptions towards the YouTube Video Project as measured by the five attitudinal dimensions of enjoyment, engagement, motivation, behavioral intention and perceived effectiveness. The YouTube Video Project facilitated learning in two ways: through repetition practice, and through the use of vocabulary in real-life tasks that promote students’ productive knowledge. The main advantages that students found were increased vocabulary to support their speaking skills and greater self-confidence from publishing videos on YouTube. However, students also struggled with problems such as pronunciation and technical problems in making the videos. Hence, this study proves that the YouTube Video Project is an effective and fun learning method to improve English vocabulary mastery, and recommends that it continues to be integrated into English language learning at senior high school level